Information Technology Capability and Firm Performance: A Longitudinal Study - Daesung Ha (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- We investigate the relationship between information technology (IT) capability and firm performance of US firms during 1989-2012. Motivation- We identify the model misspecification and estimation problems in Santhanam and Hartono (2003), Chae et al. (2014), Choi and George (2016), and Rahman and Zhao (2020) and provide new estimation results by using model specifications that better fit the characteristics of the sample data. Idea- We compare the long-term trends of the IT capability-performance relationship between the IT leader and control groups. Data- All data are from InformationWeek (IW) 500 and the Compustat database. Tools- We use a dynamic panel model with the firm-specific effect which incorporates the main assumptions of the resource-based view (RBV) of the firm. Findings- We find a positive association between IT capability and firm performance by using 1,308 IT leader firms chosen from the IW 500 from the period 1989 to 2012. We also find that the IT leader group's financial performance consistently outperformed that of the control group over the entire sample period. However, during the second half of the 1990s, a period marked by a significant increase in IT proliferation and investment, the financial performance of the IT leader group leveled off. It appears that, contrary to expectations, the returns to the IT leader group's superior IT capability did not translate into substantial improvements in operational efficiency during that period. We also observe that the financial performance of the control group experienced a much stronger recovery (with a threefold increase in magnitude) compared to the IT leader group during the 2000s. Contribution- This study makes a significant contribution to the existing literature as it presents the first-ever longitudinal study on the IT capability-performance relationship spanning 24 years. Moreover, this study is the first to investigate the existence of any changes in patterns of the IT capability-performance relationship, both across different groups and over time.
Keywords: M41; 650; Resource-based view; IT capability; firm performance; dynamic panel model